Desain Pembelajaran Materi Sistem Persamaan Linear Dua Variabel dengan Konteks Wisata Jakabaring Palembang - Utami, Marta Risa Putri; Zulkardi, Zulkardi; Susanti, Ely; Meryansumayeka, Meryansumayeka (Edumatica : Jurnal Pendidikan Matematika, 2024)
The System of Linear Equations in Two Variables (SLETV) is one of the essential topics in mathematics that often presents challenges for students to understand. Interventions in the learning process can be made by designing a Hypothetical Learning Trajectory (HLT) based on Indonesian Realistic Mathematics Education (PMRI), integrating local context to enhance student understanding. This study aims to describe the design of an HLT for the SLETV topic using the context of Jakabaring tourism in Palembang, which is relevant to students' daily lives. The method used is design research, consisting of three stages: preliminary design, design experiment (pilot experiment and teaching experiment), and retrospective analysis. The subjects of this study are 30 eighth-grade students from SMPN 9 Palembang. Data were collected through observations, interviews, and documentation. The HLT was compared with the Local Instructional Theory (LIT) that emerged during the learning process. The study results show that using the Jakabaring tourism context can facilitate students in understanding the SLETV concepts, formulating mathematical models from contextual problems, and solving these problems systematically while also introducing the relevance of SLETV to real-life situations.